Resident-as-teacher to provide multidisciplinary online medical education on Instagram - Liu, Chaocheng; Sharma, Sanjay (Canadian Medical Education Journal, 2021)
Implication Statement Instagram is an easy-to-use smartphone-based program and an increasingly popular platform for medical education. A total of 17 weekly structured resident-led education sessions that cover 15 different medical specialities were hosted on an Instagram account (@medskldotcom) to publish clinical “pearls” – short pieces of free standing, evidence-based, clinically relevant information designed specifically for medical students. With the cancellations of out-of-province clerkship electives during COVID-19 pandemic, the number of resident-led Instagram accounts to promote residency programs have increased. Our initiative can be easily adapted by residents or even clinicians to provide medical education to medical students, showcase residents, and attract followers on Instagram.